"Prospective study of outcome of 480 arteriovenous fistulas in patient with end stage renal disease" - A single center experience (Journal of Dhaka National Medical College & Hospital, 2017)
Background: Patients with End Stage Renal Disease Undergo artereovenous fistulas for Haemodialysis with variable outcomes.Aims: The arteriovenousfistal is the preferred vascular access for haemodialysis in patients with end stage renal disease. This prospective study was aimed to evaluate the outcome, patency predictors & primary failure rate of 480 arteriovenous fistulas.Materials and Methods: This prospective study was conducted at Kidney Foundation Hospital & Research Institute, Dhaka, Bangladesh from 1st January, 2014 through 31st December, 2014. 480 patients age ranged from 14 to 70 years with End Stage Renal Disease were included in this study. The patients who died or lost during this period were excluded from this study. All patients before surgery, underwent thorough relevant medical history, physical examination that included examination of upper limb arterial pulses, blood pressure, body temperature, oedema, etc. Left upper limb was chosen for 370 patients and right upper limb was chosen for 110 patients.Results: Majority of the patients (73%) were between the age of 40 to 70 years and male patients were predominant (56.25%) out of total 480 patients. Twenty four (5%) patients had primary failure, Fifty eight (12.08%) patients had secondary failure. So, total failure rate was 17.08%. Remaining 398 (82.92%) arteriovenousfistula were suitable for haemodialysis during this study period. The causes of AVF failure were thrombosis, aneurysm, stenosis, infection &haemorrhage.Conclusion: Haemodialysis remains the commonest mode of renal replacement therapy for end stage renal disease patients. Arteriovenous fistula is the reliable mode of vascular access for haemodialysis in end stage renal disease patients. A good functioning AVF provides effective haemodialysis with fewer risk & complications. Effort should therefore be made to give knowledge for the doctors, dialysis staff and patients to achieve a more successful outcome.J. Dhaka National Med. Coll. Hos. 2017; 23 (01): 12-15